2021
DOI: 10.22271/oral.2021.v7.i3b.1281
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric dentistry: Glass ionomer or giomer?

Abstract: Introduction: Giomers are composed of PRG fillers which in turn contain some ions, in addition to fluoride, which are beneficial to enamel so, it could be used for remineralization. Glass ionomer also contains fluoride and has been a commonly used material for many years. Objective: to analyze information about its chemical composition, physical properties, chemical properties and application of S-PRG technology in comparison with glass ionomer. Methodology: articles were searched in PubMed, Science Direct, Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…When examining the impact of the restrictive measures during the COVID-19 pandemic on bruxism, we did not find an increase in the frequency of occurrence or aggravation of an already existing bruxism in the examined children. In contrast to the present one, other studies have found an increase in the likelihood of bruxism during the pandemic [8][9][10][11][12][13]. The increase is due to increased levels of stress, anxiety, reduced physical activity and increased screen time during the pandemic, which, individually and/or in combination, may be risk factors for sleep bruxism.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…When examining the impact of the restrictive measures during the COVID-19 pandemic on bruxism, we did not find an increase in the frequency of occurrence or aggravation of an already existing bruxism in the examined children. In contrast to the present one, other studies have found an increase in the likelihood of bruxism during the pandemic [8][9][10][11][12][13]. The increase is due to increased levels of stress, anxiety, reduced physical activity and increased screen time during the pandemic, which, individually and/or in combination, may be risk factors for sleep bruxism.…”
Section: Discussioncontrasting
confidence: 88%
“…The increase is due to increased levels of stress, anxiety, reduced physical activity and increased screen time during the pandemic, which, individually and/or in combination, may be risk factors for sleep bruxism. [7][8][9][10][11][12][13]. Although in their research, Nazzal et al found only 5.7% of children with bruxism, examining some of the above factors during the pandemic, found that the risk of adverse consequences for orofacial structures was increased [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, regular evaluation of materials and reinforcement of preventive measures in the patient, as well as assessment of the oral health conditions, is crucial. Giomers can also be utilized in patients with Molar Incisor Hypomineralization (MIH), as they can control sensitivity while simultaneously remineralizing the affected tooth's surface (Bernal et al, 2021). Kaga et al (2014) investigated giomers' capacity and inhibitory effects on enamel demineralization and found that giomers neutralize the pH of solutions and protect enamel from demineralization by releasing modest amounts of Si, Sr, Al, B, Na, and F ions (Kaga et al, 2014).…”
Section: Discussionmentioning
confidence: 99%